Pathogenicity of different pathogens on Arabidopsis thaliana - JEAN-PIERRE HERNALSTEENS, N.P. ESWARA REDDY* and (Indian Phytopathology, 2002)
The pathogenicity of plant pathogens to Arabidopsis thaliana was investigated. Among the plant pathogens tested, Agrobacterium tumefaciens, Erwinia chrysanthemi, Rhizoctonia solani, Sclerotinia minor and Botrytis cinerea showed a compatible interaction and produced characteristic symptoms. The 2 strains of Fusarium, namely, F. oxysporum f.sp. ciceris and F. o. f.sp. radicis-lycopersici showed an incompatible interaction. Replication of the tobacco mosaic tobamovirus cowpea strain (TMVCc) was not detected.